The Role of Crisis Management Strategies in Ensuring the Organizational Resilience of Multipurpose Cooperative in Davao Del Norte - Flores, Joe Mari N.; Delgado, Shyra Kate C.; Febrero, Rena Mae L.; Naces, Khaila G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study investigates the role of crisis management strategies in enhancing the resilience of multipurpose cooperatives in Davao del Norte. Specifically, it explores the effectiveness of prevention, cooperation, containment, and confrontation in addressing operational disruptions and sustaining organizational stability. Given the unpredictable nature of crises, the study aligns with Sustainable Development Goals (SDG) 8 (Decent Work and Economic Growth) and SDG 9 (Industries, Innovation, and Infrastructure), emphasizing the importance of resilient cooperative infrastructures in fostering economic growth and industrial innovation. The research utilized convenience sampling to survey 205 respondents from a population of 92 cooperatives through face-to-face structured questionnaires. Findings revealed a significant relationship between crisis management strategies and organizational resilience. Regression analysis showed that cooperation, containment, and confrontation significantly influenced resilience (p < 0.05). These strategies enable cooperatives to effectively navigate crises and sustain operations. This study underscores the need for proactive and adaptable crisis management strategies to strengthen cooperative resilience, safeguard economic stability, and enhance community well-being.